Pengaruh Penerapan Model PAIKEM dipadu Media Mind Map pada Materi Sistem Ekskresi terhadap Hasil Belajar Peserta Didik Kelas XI di SMAN 1 Lambu Kabupaten Bima - Muslimah Arbiah; Ummul Hasanah; Andi Maulana (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Education plays a role in the quality of life; therefore, education must create enjoyable learning. A good learning mode is really needed to support active, effective, creative innovative and fun learning. The PAIKEM model is a learning model that reduces unpleasant learning to become enjoyable. The research aims to determine the affective of applying the PAIKEM model combined with mind map media on excretory system material on the learning outcomes of class XI MIA students at SMAN 1 Lambu, BIMA regency. The research population was class XI MIA at SMAN I Lambu, totaling 90 people. The sample consisted of 62 students, using purposive sampling. The instrument used were learning outcomes tests, observation and interviews. The analysis techniques used are descriptive statistical analysis and inferential statistical analysis research, a sig of 0,000 was obtained, indicating that sig a = 0,000 < 0,05, so that H 0 was rejected and H1 was accepted. The results show that there is a significant influence from the application of the PAIKEM model combined with mind map media in the excretion system material on the learning outcomes of class XI MIA students at SMAN 1 Lambu, Bima Regency. The implication of this research is that the PAIKEM model can be applied to increase creative, innovative and enjoyable learning.